'That's how Muslims are required to view the world': Race, culture and belief in non-Muslims' descriptions of Islam and science. Issue 1 (January 2019) - Jones, Stephen H.; Catto, Rebecca; Kaden, Tom; Elsdon-Baker, Fern
Islam's positioning in relation to Western ideals of individuality, freedom, women's rights and democracy has been an abiding theme of sociological analysis and cultural criticism, especially since September 11 2001. Less attention has been paid, however, to another concept that has been central to the image of Western modernity: science. This article analyses comments about Islam gathered over the course of 117 interviews and 13 focus groups with non-Muslim members of the public and scientists in the UK and Canada on the theme of the relationship between science and religion. The article shows how participants' accounts of Islam and science contrasted starkly with their accounts of other religious traditions, with a notable minority of predominantly non-religious interviewees describing Islam as uniquely, and uniformly, hostile to science and rational thought. It highlights how such descriptions of Islam were used to justify the cultural othering of Muslims in the West and anxieties about educational segregation, demographic 'colonization' and Islamist extremism. Using these data, the article argues for: (1) wider recognition of how popular understandings of science remain bound up with conceptions of Western cultural superiority; and (2) greater attentiveness to how prejudices concerning Islamic beliefs help make respectable the idea that Muslims pose a threat to the West.